XRD and HREM studies from the decomposition of icosahedral AlCuFe single-phase by high-energy ball milling - Patiño-Carachure, C.; Téllez-Vázquez, O.; Rosas, G. (Journal of alloys and compounds, 2011)
► Point defects induced during milling leading to an order–disorder quasicrystal transition. ► Nanoquasicrystalline regions of 12 nm are obtained. ► Highly ordered i-phase with high symmetry transforms to a crystalline phase of intermetallic character and lower symmetry. In this investigation the Al 64Cu 24Fe 12 alloy was melted in an induction furnace and solidified under normal casting conditions. In order to obtain the icosahedral phase (i-phase) in a single-phase region, the as-cast sample was subject to a heat treatment at 700 °C under argon atmosphere. Subsequently, the i-phase was milled for different times in order to evaluate phase stability under heavy deformation. X-ray diffraction (XRD) and high-resolution electron microscopy (HREM) analysis were conducted to the structural characterization of ball-milled powders. XRD results indicated a reduction in quasicrystal size during mechanical ball milling to about 30 h. HREM analysis revealed the presence of aperiodic nano-domains, for example, with apparent fivefold symmetry axis. Therefore, the i-phase remains stable over the first 30 h of ball-milling time. However, among 30–50 h of mechanical milling the i-phase transforms progressively into β-cubic phase.